Efektivitas Pelaksanaan Penilaian Matematika Madarasah Ibtidaiyah Swasta (MIS) Al-Ikhlas Rum di Masa Pandemi Covid-19 - Muhlis Malaka; Rosdiana Im; Alfian Alfian; Yani Djawa; Tamrin Taher (Peneliti.net, 2022)
The Covid-19 pandemic has brought changes to various aspects of the world of education, including learning activities and evaluation. This research aims to; 1) Describe the implementation of assessments in learning mathematics during the Covid-19 pandemic, 2) Knowing the effectiveness of implementing assessments of student mathematics learning outcomes during the Covid-19 pandemic. This research was conducted at Al-Ikhlas Rum Private Islamic Elementary School (MIS), North Tidore District, Tidore City, North Maluku Province, Academic Year 2020/2021. The subjects of the study were fifth grade students, teachers and principals of the MIS Al-Ikhlas Rum Madrasah. This research is an evaluation research with a quantitative descriptive approach. Data collection techniques using tests, interviews and documentation. Data were analyzed quantitatively and descriptively. Quantitative analysis includes the normality test and paired test, while the description of the data is carried out based on the results of interviews and documentation. The results of the study showed that learning during the pandemic at Al-Ikhlas Rum Private Madrasah Ibtidaiyah was carried out using the online method, dividing the classes into two classes, and offline learning by visiting students to their homes. The results of the paired simple test show that the sig (2-tailed) value is 0.000 or less than 0.005. Thus it can be concluded that there is a significant difference between the results of learning mathematics in the pre-test and post-test data